Hey there!
“Which expression is equivalent to b + b – 0.56b?”
• “b” or any other letter value is considered an “unknown number” so usually we label it/them as an invisible 1
• COMBINE the LIKE TERMS
(b + b – 0.56b)
(1b + 1b – 0.56b)
1b + 1b = 2b
2b – 0.56b = 1.44b
• Therefore, b + b – 0.56b is equivalent to 2b + 0.56b
Possible answer that you could be looking for: 2b + 0.56b ☑️
Good luck on your assignment and enjoy your day!
~LoveYourselfFirst:)
Answer:
![x = 48 \: \: \: \: \: \: y = 16](https://tex.z-dn.net/?f=x%20%3D%2048%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20y%20%3D%2016)
Step-by-step explanation:
![y = - x + 4y](https://tex.z-dn.net/?f=y%20%3D%20%20-%20x%20%2B%204y)
![y + x = 4y](https://tex.z-dn.net/?f=y%20%2B%20x%20%3D%204y)
![y + x - 4y = 0](https://tex.z-dn.net/?f=y%20%2B%20x%20-%204y%20%3D%200)
![- 3y + x = 0](https://tex.z-dn.net/?f=%20-%203y%20%2B%20x%20%3D%200)
![- x + 4y = 16](https://tex.z-dn.net/?f=%20-%20x%20%2B%204y%20%3D%2016)
![- 3y + x = 0](https://tex.z-dn.net/?f=%20-%203y%20%2B%20x%20%3D%200)
![- 3y = - x](https://tex.z-dn.net/?f=%20-%203y%20%3D%20%20-%20x)
![y = - \frac{1}{3} ( - 1)x](https://tex.z-dn.net/?f=y%20%3D%20%20-%20%20%5Cfrac%7B1%7D%7B3%7D%20%28%20-%201%29x)
![y = \frac{1}{3} x](https://tex.z-dn.net/?f=y%20%3D%20%20%5Cfrac%7B1%7D%7B3%7D%20x)
![4 \times ( \frac{1}{3} )x - x = 16](https://tex.z-dn.net/?f=4%20%5Ctimes%20%28%20%5Cfrac%7B1%7D%7B3%7D%20%29x%20-%20x%20%3D%2016)
![\frac{1}{3}x = 16](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B3%7Dx%20%3D%2016%20)
![x = 48](https://tex.z-dn.net/?f=x%20%3D%2048)
![y = \frac{1}{3} \times 48](https://tex.z-dn.net/?f=y%20%3D%20%20%5Cfrac%7B1%7D%7B3%7D%20%20%5Ctimes%2048)
![y = 16](https://tex.z-dn.net/?f=y%20%3D%2016)
Hope this is correct and helpful
HAVE A GOOD DAY!
Answer:
in 14 years Julio will be 50 and James will be 25
Answer:
4x-3y-51=0
Step-by-step explanation:
y-
=m(x-
)
y-(-9) =
(x-6)
3y+27=4x-24
4x-3y-51=0